Implementing a Cutting-Edge Recycling Web Application for Sustainable Progress in Tha Pho Sub-district: Empowering Residents and Recycling Industry Partners - Kruayim, Sariya; Liampreecha, Wasin; Chaisri, Suttida (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 3 (2024): July - September 2024, 2024)
This article explores the integration of circular business practices into sustainable digital entrepreneurship in Tha Pho district, Phitsanulok province, addressing local waste management challenges through a design thinking approach. By considering the local context, cultural nuances, and technological infrastructure, the study aims to create a user-friendly and effective platform. The design process involves prototyping, allowing for iterative feedback and customization through rigorous testing with community members, stakeholders, and waste management entities. This ensures that the platform meets local requirements and motivations, encouraging participation, collaboration, and sustainable digital practices. The goal is to foster engagement, promote sustainable behaviors, and utilize local resources to create an environmentally conscious digital landscape in Tha Pho. The study highlights the significance of user-centered design in developing efficient solutions for sustainable recycling practices. The research findings demonstrate high satisfaction with the NUZeroWaste Web application, with students giving an overall score of 4.00 and university outsiders rating it 4.42. Key benefits reported include improved accessibility to recycling knowledge, streamlined processes, and real-time feedback. The application also significantly reduced errors and negative feedback, showcasing its effectiveness over conventional methods. Overall, the NUZeroWaste Web application successfully enhanced recycling practices and promoted long-term sustainable behavior, underscoring its potential to address community-specific challenges in waste management. Keywords:  Phitsanulok, Recycling Business, Digital Entrepreneurship, Sustainable Development Goals , Web Application, Community Participation